The clinical significance of intrapulpal anesthesia for painless dental procedure - Burić Nina N.; Stojanović Simona M.; Burić Kristina N. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2020)
Introduction:The elimination of odontalgia and all other forms of oral pain that occurs on dental tissues during dental interventions is still one of the main goals in the dental profession. Aim: The aim of this paper wasto perform an analysis of the literature data on the use of supplementary intrapulpal anesthesia in clinical dental practice. Material and methods: Literature data on the use of intrapulpal anesthesia, the characteristics of this technique of supplementary anesthesia as well as the results of its application were collected. Various databases were used for this purpose, digital data from Google Scholar, Medline, Science-Direct, as well as traditional libraries with manuscripts in printed form were most often taken. Conclusion: The use of supplementary intrapulpal anesthesia in dental/endodontic practice represents a practical and successful type of local anesthesia, when standard mandibular anesthesia for the lower alveolar nerve does not provide a deep enough periinterventional analgesia for dental procedures.